Kekuatan Lentur dan Kekuatan Impak Komposit Matrik Epoxy Berpenguat Serat Sisal (Agave Sisalana) Menggunakan Metode Vacuum Bagging - Asrian, Angga; Putri Nawangsari; Fatra, Warman; Masnur, Dedy (Fakultas Teknik UMRI, 2025)
Agave Sisalana is widely grown in the Bukit Bulek area, West Sumatra Province. The Sisal leaf fiber is traditionally utilized by the Bukit Bulek community as a rope material. This indicates it has a great potential to be developed as a composite reinforcement material. This research aims to characterize the flexural and impact strength of Sisal leaf fiber as reinforcement in epoxy matrix composites by varying the fiber volume fractions, 30%, 35%, 40%, and 45% with a 0°/90° fiber orientation laminate. The 20 cm long of fibers and treated with 5% NaOH alkaline solution for 4 hours were employed. The composites were fabricated using the vacuum bagging method. Flexural and impact tests were conducted based on ASTM D-790 and ASTM D-6110 standards, respectively. The results show that the flexural strength increases from 45,20 to 49,67 MPa (maximum) as the fiber volume fraction increases from 30% to 35% fiber. Meanwhile, the impact strength increases as fiber volume fractions from 30% to 45% and reaches a maximum impact strength of 24.60 kJ/m².